The Role and Impact of ATMs in reducing Regional Disparities to Enhance Competitive Edge for the Indian Economy - R, Madhavi; Bansal, Divya (Ushus Journal of Business Management, 2014)
Every nation runs its economic chariot through the guidance of the banking sector. The policy makers work on the twin objectives of removing regional imbalances across the length and breadth of the country and to reach out to the underprivileged masses of the society in our country. To serve objectives with such lofty ideals, not only does profit making take a back seat, it also calls in for investment in infrastructure to enhance competitive edge to the entire sector. The power of nationalization was seen as it emerged to shift focus from ―Class Banking‖ to ―Mass banking‖, from ―Profit Banking‖ to ―Social Banking‖ and from ―Elite Banking‖ to ―Every body‘s Banking. Automated Teller Machines (ATM), Telephonic Customer Service (TCS), online banking and mobile banking are the most prominent ones amongst banking technological advances. Yet, has it really touched the heart and soul of the country? The measurable progress with its impressive numbers, guided by policy making at the centre, has churned out progress year after year and managed to hide a growing hole called the disparity in banking services between the urban and rural masses.